The impact of customer satisfaction, customer experience and customer loyalty on brand power: empirical evidence from hotel industry - Nobar, Hossein Bodaghi Khajeh; Rostamzadeh, Reza (Journal of Business Economics and Management, 2018)
This research aims to investigate the impact of customer satisfaction, experience, and loyalty on brand power in the Hotel industry. This study used a descriptive-survey research design based on the correlation method. The selected populations were Pars Hotels’ customers. Sample size was 384, based on Krejcie and Morgan’s sampling table. The structural equation modeling was used to evaluate the causal simulation and to examine the reliability and validity of the measuring model. The research results showed that customer expectation has the most impact on customer satisfaction with path coefficient of 0.74. On the other hand, customer loyalty, with path coefficient of 0.65, is known as an influential factor. This study helps to understand that customer satisfaction and customer expectations are positive drivers of customer loyalty. Customer loyalty also is a strong predictor of brand power in hoteling and tourism industry. By strengthening that part, which you have better resources, you can have a better supply and thus, there would be more opportunities in establishing reputation and increasing visibility.